Staphylococcus aureus enterotoxin B disrupts nasal epithelial barrier integrity. Issue 1 (31st October 2020) - Martens, Katleen; Seys, Sven F.; Alpizar, Yeranddy A.; Schrijvers, Rik; Bullens, Dominique M. A.; Breynaert, Christine; Lebeer, Sarah; Steelant, Brecht
Abstract: Background: Staphylococcus aureus colonization and release of enterotoxin B (SEB) has been associated with severe chronic rhinosinusitis with nasal polyps (CRSwNP). The pathogenic mechanism of SEB on epithelial barriers, however, is largely unexplored. Objective: We investigated the effect of SEB on nasal epithelial barrier function. Methods: SEB was apically administered to air‐liquid interface (ALI) cultures of primary polyp and nasal epithelial cells of CRSwNP patients and healthy controls, respectively. Epithelial cell integrity and tight junction expression were evaluated. The involvement of Toll‐like receptor 2 (TLR2) activation was studied in vitro with TLR2 monoclonal antibodies and in vivo in tlr2 −/− knockout mice. Results: SEB applied to ALI cultures of polyp epithelial cells decreased epithelial cell integrity by diminishing occludin and zonula occludens (ZO)‐1 protein expression. Antagonizing TLR2 prevented SEB‐induced barrier disruption. SEB applied in the nose of control mice increased mucosal permeability and decreased mRNA expression of occludin and ZO‐1, whereas mucosal integrity and tight junction expression remained unaltered in tlr2 −/− mice. Furthermore, in vitro SEB stimulation resulted in epithelial production of IL‐6 and IL‐8, which was prevented by TLR2 antagonization. Conclusion & Clinical relevance: SEB damages nasal polyp epithelial cell integrity by triggering TLR2 in CRSwNP. Our results suggest that SEB might represent a driving factor of disease exacerbation, rather than a causal factor for epithelial defects in CRSwNP. Interfering with TLR2 triggering might provide a way to avoid the pathophysiological consequences of S. aureus on inflammation in CRSwNP.